Past, present, and future: Trajectories in Kittler studies. Issue 3 (2nd July 2016) - Scott, Patrick
ABSTRACT: Following his death in 2011, there has been a spate of publications on the work of Friedrich Kittler. This review essay discusses The Truth of the Technological World (2013), Kittler Now: Current Perspectives in Kittler Studies (2015), and Media After Kittler (2015). These three recently published collections feature essays that cover the history of Kittler's writing, and trace out the debates about the significance of technical operation to the effects of media. Most importantly, the exegetical essays in these volumes signal a shift from earlier efforts to introduce Kittler's writings towards a more robust conceptualization of how his work might benefit English-language theorizations of the contemporary media situation.